Congenital heart defects in molecularly confirmed KBG syndrome patients. Issue 4 (31st December 2021) - Digilio, Maria Cristina; Calcagni, Giulio; Gnazzo, Maria; Versacci, Paolo; Dentici, Maria Lisa; Capolino, Rossella; Sinibaldi, Lorenzo; Baban, Anwar; Putotto, Carolina; Alfieri, Paolo; Unolt, Marta; Lepri, Francesca R.; et al.
Abstract: Congenital heart defects (CHDs) are known to occur in 9%–25% of patients with KBG syndrome. In this study we analyzed the prevalence and anatomic types of CHDs in 46 personal patients with KBG syndrome, carrying pathogenetic variants in ANKRD11 or 16q24.3 deletion, and reviewed CHDs in patients with molecular diagnosis of KBG syndrome from the literature. CHD was diagnosed in 15/40 (38%) patients with ANKRD11 variant, and in one patient with 16q24.3 deletion. Left ventricular outflow tract obstructions have been diagnosed in 9/15 (60%), subaortic or muscular ventricular septal defect in 5/15 (33%), dextrocardia in 1/15 (8%). The single patient with 16q24.3 deletion and CHD had complete atrioventricular septal defect (AVSD) with aortic coarctation. Review of KBG patients from the literature and present series showed that septal defects have been diagnosed in 44% (27/61) of the cases, left ventricular tract obstructions in 31% (19/61), AVSD in 18% (11/61). Septal defects have been diagnosed in 78% of total patients with 16q24.3 deletion. Valvar anomalies are frequently diagnosed, prevalently involving the left side of the heart. A distinctive association with AVSD is identifiable and could represent a marker to suggest the diagnosis in younger patients. In conclusion, after precise molecular diagnosis and systematic cardiological screening the prevalence of CHD in KBG syndrome seems to be higher than previously reported in clinical articles. In addition to septal defects, left‐sided anomalies and AVSD should be considered. Clinical management of KBG syndrome should include accurate and detailed echocardiogram at time of diagnosis.